Skeletal adaptation to mechanical cues during homeostasis and repair: the niche, cells, and molecular signaling - Atria, P. J.; Castillo, A. B. (Frontiers in Physiology, 2023)
Bones constantly change and adapt to physical stress throughout a person`s life. Mechanical signals are important regulators of bone remodeling and repair by activating skeletal stem and progenitor cells (SSPCs) to proliferate and differentiate into bone-forming osteoblasts using molecular signaling mechanisms not yet fully understood. SSPCs reside in a dynamic specialized microenvironment called the niche, where external signals integrate to influence cell maintenance, behavior and fate determination. The nature of the niche in bone, including its cellular and extracellular makeup and regulatory molecular signals, is not completely understood. The mechanisms by which the niche, with all of its components and complexity, is modulated by mechanical signals during homeostasis and repair are virtually unknown. This review summarizes the current view of the cells and signals involved in mechanical adaptation of bone during homeostasis and repair, with an emphasis on identifying novel targets for the prevention and treatment of age-related bone loss and hard-to-heal fractures.